Sugar-sweetened beverage (SSB) consumption, correlates and interventions among Australian Aboriginal and Torres Strait Islander communities: a scoping review. Issue 2 (27th February 2019) - Wright, Kathleen M; Dono, Joanne; Brownbill, Aimee L; Pearson (nee Gibson), Odette; Bowden, Jacqueline; Wycherley, Thomas P; Keech, Wendy; O'Dea, Kerin; Roder, David; Avery, Jodie C; Miller, Caroline L
Abstract : Objectives: Sugar-sweetened beverage (SSB) consumption in Australian Aboriginal and Torres Strait Islander people is reported to be disproportionally high compared with the general Australian population. This review aimed to scope the literature documenting SSB consumption and interventions to reduce SSB consumption among Australian Aboriginal and Torres Strait Islander people. Findings will inform strategies to address SSB consumption in Aboriginal and Torres Strait Islander communities. Methods: PubMed, SCOPUS, CINAHL, Informit, Joanna Briggs Institute EBP, Mura databases and grey literature were searched for articles published between January 1980 and June 2018. Studies were included if providing data specific to an Australian Aboriginal and/or Torres Strait Islander population's SSB consumption or an intervention that focused on reducing SSB consumption in this population. Design: Systematic scoping review. Results: 59 articles were included (1846 screened). While reported SSB consumption was high, there were age-related and community-related differences observed in some studies. Most studies were conducted in remote or rural settings. Implementation of nutrition interventions that included an SSB component has built progressively in remote communities since the 1980s with a growing focus on community-driven, culturally sensitive approaches. More recent studies have focused exclusively on SSB consumption. Key SSB-related intervention elements included incentivising healthier options; reducing availability of less-healthy options; nutrition education; multifaceted or policy implementation (store nutrition or government policy). Conclusions: There was a relatively large number of studies reporting data on SSB consumption and/or sales, predominantly from remote and rural settings. During analysis it was subjectively clear that the more impactful studies were those which were community driven or involved extensive community consultation and collaboration. Extracting additional SSB-specific consumption data from an existing nationally representative survey of Aboriginal and Torres Strait Islander people could provide detailed information for demographic subgroups and benchmarks for future interventions. It is recommended that a consistent, culturally appropriate, set of consumption measures be developed.